Inclusão informacional de comunidades mediada pela responsabilidade social - Farias, Maria Giovanna Guedes (2011)
The informational inclusion provides opportunities for social inclusion through the work of the Information Science professionals based on the social responsibility. In this sense we developed a research during the Masters Postgraduate Program in Information Science at the Federal University of Paraíba to intervene in the process of informational exclusion experienced by the Community Santa Clara (CSC) in João Pessoa. The intervention happened through field research for registration, organization and dissemination of "information sources" comprised of people of the Community. An action of information has been implemented into the CSC to create the virtual interface "Blog da Comunidade Santa Clara" to disseminate the wealth of knowledge of those depositors of social memory and knowledge of Santa Clara. The result of the research was increased, in reciprocal action of the Community and as assumption of the action-research-methodology, the determination to continue the publication of the blog (a virtual interface for communication of information).